Abaloparatide exhibits greater osteoanabolic response and higher cAMP stimulation and β‐arrestin recruitment than teriparatide. Issue 19 (29th September 2019) - Sahbani, Karim; Cardozo, Christopher P.; Bauman, William A.; Tawfeek, Hesham A.
Abstract: Teriparatide and abaloparatide are parathyroid hormone receptor 1 (PTHR1) analogs with unexplained differential efficacy for the treatment of osteoporosis. Therefore, we compared the effects of abaloparatide and teriparatide on bone structure, turnover, and levels of receptor activator of nuclear factor‐kappa B ligand (RANKL) and osteoprotegerin (OPG). Wild‐type (WT) female mice were injected daily with vehicle or 20–80  µ g/kg/day of teriparatide or abaloparatide for 30 days. Femurs and spines were examined by microcomputed tomography scanning and serum levels of bone turnover markers, RANKL, and OPG, were measured by ELISA. Both analogs similarly increased the distal femoral fractional trabecular bone volume, connectivity, and number, and reduced the structure model index (SMI) at 20–80  µ g/kg/day doses. However, only abaloparatide exhibited a significant increase (13%) in trabecular thickness at 20  µ g/kg/day dose. Femoral cortical evaluation showed that abaloparatide caused a greater dose‐dependent increase in cortical thickness than teriparatide. Both teriparatide and abaloparatide increased lumbar 5 vertebral trabecular connectivity but had no or modest effect on other indices. Biochemical analysis demonstrated that abaloparatide promoted greater elevation of procollagen type 1 intact N‐terminal propeptide, a bone formation marker, and tartrate‐resistant acid phosphatase 5b levels, a bone resorption marker, and lowered the RANKL/OPG ratio. Furthermore, PTHR1 signaling was compared in cells treated with 0–100 nmol/L analog. Interestingly, abaloparatide had a markedly lower EC50 for cAMP formation (2.3‐fold) and β ‐arrestin recruitment (1.6‐fold) than teriparatide. Therefore, abaloparatide‐improved efficacy can be attributed to enhanced bone formation and cortical structure, reduced RANKL/OPG ratio, and amplified Gs‐cAMP and β ‐arrestin signaling. Abstract : Using a mouse model, we demonstrate that the skeletal response to abaloparatide treatment was more amplified compared to teriparatide‐treated animals. A daily regimen of abaloparatide administration caused a larger increase in trabecular and cortical bone thickness and higher bone formation than teriparatide. In vitro studies further demonstrated that abaloparatide activation of PTHR1 produces more efficient coupling of PTHR1 to Gs‐cAMP and β ‐arrestin signaling mechanisms than that for teriparatide.